Stock Valuation Analysis Of LQ45 Companies: Free Cash Flow To Equity (FCFE) And Price To Earningratio (PER) Methods (2020-2024) - Andi Maulidyah; Rusdi Raprayogha; Eka Indriyani MS (International Journal of Education Management and Religion, 2026)
This study aims to analyze the fair value of stocks of companies listed in the LQ45 Index on the Indonesia Stock Exchange (IDX) during the 2020–2024 period using the Free Cash Flow to Equity (FCFE) and Price to Earnings Ratio (PER) methods. The main objective of this research is to provide a more comprehensive understanding of stock valuation methods that can support investors in making informed investment decisions. This research employs a descriptive quantitative method with a purposive sampling technique, resulting in 18 selected companies that consistently met the LQ45 index criteria during the study period. Data were collected from secondary sources, including financial statements, cash flow reports, and stock price data obtained from the IDX and other official financial platforms. The valuation using the FCFE method focuses on estimating intrinsic value based on projected free cash flow available to equity holders, discounted by the cost of equity, while the PER method applies a relative valuation through earnings multiples.The findings reveal differences in intrinsic value results between the two methods. Several stocks are identified as undervalued and overvalued, indicating that each valuation method provides unique perspectives: FCFE reflects a cash flow–based valuation, whereas PER emphasizes profitability ratios in the market context. The results also highlight that combining both valuation approaches can offer a more balanced investment analysis.In conclusion, this study confirms that intrinsic value analysis through FCFE and PER can serve as an effective decision-making tool for investors, particularly in volatile capital market conditions. The findings contribute to the development of valuation strategies for investment planning and portfolio management, especially for stocks with large market capitalization and high liquidity in the Indonesian capital market.